The relationship between personality traits and dysfunctional attitudes of medical staff in the pandemic period - Sandu, Mihaela; Enache, Rodica Gabriela; Ariciu, Stefania; Burtea, Cristina; Pantea, Stefania (Technium Social Sciences Journal, 2021)
In recent years, the study of medical employees’ mental health has become an important debated topic in the literature around the world, but little information is available on the extent to which social, psychological, and organizational factors affect the degree of exhaustion, leading to behavioral changes. The pandemic period that has affected (negatively impacted) the whole world in the last year, represented even more a degree of stress for the medical staff, who imminently and directly confronted the biological enemy. Medical employees are frequently exposed to both physical and mental risks. Shocking events and the likelihood of failure encountered during the work schedule can cause mental changes and an emotional imbalance.